ALIH KODE DALAM PROSES PEMBELAJARAN BAHASA INGGRIS DI SMA - Margana Margana (LITERA, 2013)
This study aims to describe code switching in classroom communication from the sociolinguistic point of view. The research subjects comprised 12 English teachers in senior high schools in the Province of Yogyakarta Special Territory. The data were code switching utterances from English to Indonesian and vice versa in English language learning in the classroom. The data were analyzed using the qualitative descriptive method. The findings show that code switching has three functions, i.e. (a) material delivery, (b) classroommanagement, and (3) discourse markers. With reference to such functions, code switching in English language learning can be made as far as it satisfies academic functions. As the students’ English mastery improves, the use of code switching needs to be reduced.